Designing Improvements To The Product Attributes Of Samase Koko Clothes Based On Consumer Preferences Using The Conjoint Analysis Method - Shania Salsabila; Boby Hera Sagita; Sari Wulandari (Publikasi Indonesia, 2023)
Samase is one of the MSMEs from Bandung that was established in 2014. Samase is engaged in fashion, especially men's Muslim clothing. One of its superior products is koko clothes consisting of koko shirts and koko kurta, but the sales of koko clothes have not been able to meet the set target, this is due to product attributes that are not by consumer desires. This study aims to formulate a combination of attributes and the level of attributes on Samase koko shirt products that are considered important by consumers, by compiling recommendations for improving the right koko clothes attributes according to consumer desires and comparing them with existing attributes. The questionnaire in this study was distributed online to consumers who had bought and used koko clothes products from Samase, totaling 108 respondents. The results of the questionnaire were processed using conjoint analysis to determine consumer preferences. Based on calculations using conjoint analysis, it is known that consumer preferences with the highest utility value are, supernova material, long sleeve size, koko shirt model, deep color, basic collar, printing motifs, and price in the range of Rp. 200,000 - Rp. 300,000